Perfluorocarbon Nanoemulsions Enhance Therapeutic siRNA Delivery in the Treatment of Pulmonary Fibrosis. Issue 8 (7th January 2022) - Ding, Ling; Tang, Siyuan; Tang, Weimin; Mosley, Deanna D.; Yu, Ao; Sil, Diptesh; Romanova, Svetlana; Bailey, Kristina L.; Knoell, Daren L.; Wyatt, Todd A.; Oupický, David
Abstract: Local pulmonary administration of therapeutic siRNA represents a promising approach to the treatment of lung fibrosis, which is currently hampered by inefficient delivery. Development of perfluorooctylbromide (PFOB) nanoemulsions as a way of improving the efficiency of pulmonary polycation‐based delivery of siRNA is reported. The results show that the polycation/siRNA/PFOB nanoemulsions are capable of efficiently silencing the expression of STAT3 and inhibiting chemokine receptor CXCR4—two validated targets in pulmonary fibrosis. Both in vitro and in vivo results demonstrate that the nanoemulsions improve mucus penetration and facilitate effective cellular delivery of siRNA. Pulmonary treatment of mice with bleomycin‐induced pulmonary fibrosis shows strong inhibition of the progression of the disease and significant prolongation of animal survival. Overall, the study points to a promising local treatment strategy of pulmonary fibrosis. Abstract : This paper reports perfluorocarbon nanoemulsions capable of safe and effective pulmonary siRNA delivery with deep lung penetration and cytosolic siRNA delivery to mediate effective pulmonary STAT3 silencing and CXCR4 inhibition in pulmonary fibrosis. The reported finding may lead to a development of novel treatment of lung fibrosis via noninvasive delivery.